Development of Higher Order Thinking Skills (HOTS) Test Instruments on Dynamic Electricity Material in 9th Grade Junior High School - Riska Wahyuni; Ramlawati; Rifda Nur Hikmahwati Arif (Venn: Journal of Sustainable Innovation on Education, Mathematics and Natural Sciences, 2026)
This study aims to determine: (1) the validity of the Higher Order Thinking Skills (HOTS) instrument on dynamic electricity material; and (2) the reliability of the Higher Order Thinking Skills (HOTS) instrument on dynamic electricity material. This study employed a Research and Development (R&D) method using the ADDIE development model and was conducted up to the implementation stage. Data were collected through expert validation questionnaires to assess content validity and field testing of the HOTS instrument to obtain empirical validity and reliability data. The results showed that the instrument achieved an average content validity index of 0.9, indicating that it met the criteria for content, construction, and language validity. Of the 25 test items developed, 21 items were empirically valid and 4 items were invalid. The reliability coefficient was 0.92, indicating that the instrument was highly reliable. Therefore, the developed HOTS instrument is valid and reliable for measuring higher-order thinking skills in dynamic electricity material for ninth-grade junior high school students.